عوامل العنف الرمزي في الوسط المدرسي - بوزيدي، كنزة, جفافلة، هاجر (جامعة الوادي university of Eloued, 2019)
الملخص: تهدف هذه الدراسة إلى معرفة العوامل المساهمة في ظهور العنف الرمزي في الوسط المدرسي والتي من خلالها تم صياغة التساؤل الرئيسي على النحو التالي: ما هي عوامل العنف الرمزي في الوسط المدرسي؟ لتندرج عنه مجموعة من التساؤلات الفرعية وهي: 1- هل تساهم العوامل الأسرية في ظهور العنف الرمزي في الوسط المدرسي؟ 2- هل تساهم العوامل الاجتماعية في ظهور العنف الرمزي في الوسط المدرسي؟ 3- هل تساهم وسائل الإعلام في ظهور العنف الرمزي في الوسط المدرسي؟ 4- هل تساهم العوامل التربوية في ظهور العنف الرمزي في الوسط المدرسي؟ اعتمدت هذه الدراسة على المنهج الوصفي وأداة الاستبيان، تكونت العينة من146 تلميذ وتلميذة في جميع الشعب للسنة الثانية ثانوي بثانوية حبه عبد المجيد دائرة المغير ولاية الوادي. من خلال الدراسة الميدانية والنتائج المتحصل عليها تبين أن : العوامل الاجتماعية والتربوية تساهم بشكل كبير في ظهور العنف الرمزي في الوسط المدرسي حسب وجهة نظر المبحوثين. أما بالنسبة للعوامل الأسرية ووسائل الإعلام فهي لا تساهم بشكل كبير في ظهور العنف الرمزي في الوسط المدرسي حسب إجابات المبحوثين. Résumé :فرنسية أو انجلزية The study summary: This study aims to identify the factors contributing to the emergence of the symbolic violence in the school environment through which the main question was formulated as follows: What are the symbolic violence factors in the school environment? Under the main question there are a number of sub-questions: 1. Do family factors contribute to the emergence of symbolic violence in the school environment? 2. Do social factors contribute to the emergence of symbolic violence in the school environment? 3. Do media factors contribute to the emergence of symbolic violence in the school environment? 4 - Do educational factors contribute to the emergence of symbolic violence in the school environment? This study was based on the descriptive method using the questionnaire as a data collection tool. The sample consisted of 146 students of all the branches inHabaAbdul Majid Secondary school، district of Megheir،state of El-Ouad. Through the field study and the results obtained، the researchers found that: Social and educational factors have a significant contribution in the emergence of symbolic violence in the school environment according to the responses. Meanwhile، the family and the media factors do not contribute significantly to the emergence of symbolic violence in the school environment according to respondents' answers.
دراسة ميدانية على تلاميذ السنة ثانية ثانوي بثانوية حبه عبد المجيد دائرة لمغير ولاية الوادي
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع التربية
Keywords: العنف المدرسي، المدرسة; violence à l'école, école; school violence, school